FILSAFAT ETIKA MULLA SADRA: SINTESIS ANTARA HIKMAH MUTA'ALIYAH DAN TANTANGAN BIOETIKA KONTEMPORER - Muhammad Abrar (Yayasan An-Nur Meunara Baro, 2025)
This article explores the contribution of ethics in the philosophy of Mulla Sadra, a prominent 17th-century Islamic thinker, to contemporary bioethical dilemmas such as euthanasia, cloning, and genetic engineering. Rooted in the paradigm of Hikmah Muta‘āliyah, Sadra rejects static ethical norms and introduces a dynamic framework based on the concepts of substantial motion (al-ḥarakah al-jawhariyyah), unity of being (waḥdat al-wujūd), and gradation of existence (tashkīk al-wujūd). This approach views human existence as a process of spiritual perfection, making every ethical decision in medicine part of a broader evolution of consciousness. The study employs a qualitative method using philosophical inquiry of Sadra's primary texts and contemporary bioethical literature. Key findings reveal that Sadrian ethics offers an alternative to the fragmented and individualistic nature of Western bioethics. The concept of ontological unity allows for a reinterpretation of patient autonomy, while the gradational theory of being bridges clinical action with metaphysical values. The article recommends integrating Sadrian concepts into medical education curricula and establishing bioethics committees grounded in hikmah within Muslim contexts. The main conclusion emphasizes that Mulla Sadra’s philosophy is not merely a historical artifact but a living intellectual resource for addressing modern bioethical crises with both spiritual depth and rational coherence.